Development of Nanotechnology-Based Drug Delivery Systems for Controlling Clinical Multidrug-Resistant Staphylococcus aureus and Escherichia coli Associated with Aerobic Vaginitis - Najla Haddaji; Badr Bahloul; Wael Bahia; Olfa Bechambi; Abdelkarim Mahdhi (Pharmaceutics, 2023)
The growing prevalence of resistance to antibiotics potentially makes Escherichia coli and Staphylococcus aureus serious pathogens, necessitating the development of new antimicrobial agents. We extracted crude biosurfactants from a potential probiotic Bacillus spp. to control pathogenic bacteria associated with aerobic vaginal infection. Using nanotechnology formulations, we developed nanoemulsions based on biosurfactants at different concentrations (1% and 3.33%). The results showed that these nanoemulsions were stable, with a weighted index of 0.3, and demonstrated broad-spectrum antibacterial activity against Escherichia coli and Staphylococcus aureus, with MICs ranging between 1.25 and 4 mg/mL. Additionally, the nanoemulsions exhibited interesting antibiofilm effects. All strains became more sensitive to the antibiotics to which they were resistant because of various biosurfactant formulations combined with antibiotics. Lower concentrations of BNE1% and 3.33% were still more efficient than the crude biosurfactants. Our findings demonstrated that the biosurfactant had a strong antibiofilm effect against all tested pathogens. This antibacterial effect can be explained by their ability to alter cell physiology such as cell hydrophobicity and membrane disintegration. Thus, we can conclude that the use of nanotechnology formulations has improved this effect, and the nanoemulsions developed in this study can be used as a potential anti-infectious therapy against multidrug-resistant bacterial strains of clinical origin.